The Chemistry and Biological Effects of Fused 1,2,4-triazolo[4,3-c]pyrimidines and their Isomeric 1,2,4-triazolo[1,5-c]pyrimidines - Shamroukh, Ahmed H.; El Malah, Tamer; Rashad, Aymn E. (Current Organic Chemistry, 2025)
Concerning polycyclic heterocyclic compounds, fused triazolopyrimidines and their substituted analogs have been studied recently from a chemical and biological point of view. Triazolopyrimidines have eight different positional isomers based on their structural arrangement and nitrogen atom positions. The present review concerns synthesizing 1,2,4-triazolo[4,3-c]pyrimidines and 1,2,4-triazolo[1,5-c]pyrimidines fused with a five-membered ring containing one heteroatom. The 1,2,4-triazolo[4,3-c]pyrimidines can be prepared by closing the triazole ring on the 4-hydrazinopyrimidine ring, and the 1,2,4-triazolo[1,5-c]pyrimidines can be prepared by closing the triazole ring on the 4-iminopyrimidine-3-amine ring. The transformation of 1,2,4-triazolo[4,3-c]pyrimidine to the more thermodynamically stable isomer triazolo[1,5-c]pyrimidine derivatives via Dimroth rearrangement under different reaction conditions is also discussed. Moreover, the biological activity of both series is presented.
Keywords: thienotriazolopyrimidine